Diagnostic Imaging of Vascular Anomalies - Chaudry, M. Imran; Manzoor, Muhammad Usman; Turner, Raymond D.; Turk, Aquilla S. (Facial Plastic Surgery, 2012)
Congenital vascular anomalies are complex hereditary lesions with distinct clinical presentation, imaging, course, and treatment. We present a relevant review of the classification, pathophysiology, clinical presentation, and imaging characteristics that will allow for adequate diagnosis and understanding of these lesions.
Keywords: vascular; imaging; lesions; hereditary